Experimental characterizing combustion emissions and thermodynamic properties of a thermoacoustic swirl combustor. (1st February 2019) - Zhang, Zhiguo; Zhao, Dan; Ni, Siliang; Sun, Yuze; Wang, Bing; Chen, Yong; Li, Guoneng; Li, S.
Highlights: Equivalence ratio and methane flow rate on soot formation are experimentally examined. CO emission is found to be varied by 2 order of magnitudes. NOx and unburnt O2 are experimentally characterized in the swirl combustor. Dominant mode switching between non-harmonic frequencies is identified. Mode switching is found to depend on the equivalence ratio and the methane flow rate. Abstract: Many practical lean-premixed combustion systems involved in land-based power plants, gas turbines and boilers are susceptible to self-excited combustion instability, which is characterized by detrimental periodic pressure oscillations. Little attention has been paid on experimentally characterizing the chemical emissions and thermodynamic properties of a thermoacoustic swirl combustor. In this work, the effects of (1) fuel-air equivalence ratio Φ and fuel flow rate QCH4 on generating such combustion instability and its impact on chemical emissions and thermodynamic properties in a swirling combustor are experimentally studied. For this, a methane-fueled lab-scale swirl combustor is designed and tested. To monitor the thermodynamic properties of the combustor, an acoustic pressure sensor, an infrared thermal imaging camera, K-type thermal couples, and an infrared flue gas analyzer are applied. It is found that the fuel-air ratio plays an important role on generating combustion instability at different frequencies and amplitudes. This is confirmed by conducting autocorrelation and frequency spectrum analyses of the acoustic pressure time trace. Furthermore, the dominant mode swap (mode-switching) between a low frequency ω1 and a high non-harmonic one is experimentally observed. Whether the mode switching from high (harmonic or non-harmonic) to low frequency or low to high frequency is found to depend strongly on QCH4 . As the equivalence ratio is changed from lean to rich, i.e. 0.8 ≤ Φ ≤ 1.2, NOx emission is increased from 1 ppm to 37 ppm. However, CO emission is decreased by 2 order of magnitudes from 1000 ppm first and then increased. The minimum CO emission is approximately 3.0 ppm. In addition, O2 concentration is decreased by more than 80% with increased Φ, depending on the methane flow rate. This means that the combustion efficiency characterized by the O2 emission is decreased dramatically from 99.5% to 68% with Φ increased from 0.6 to 1.2. The present work sheds light on the characteristics of chemical emissions and thermodynamic properties, when a thermoacoustic swirl combustor is operated with methane-air equivalence ratio Φ varied from lean to rich condition and different QCH4 . It opens up a practical means to design a stably operated but low-emission thermoacoustic swirl combustor.